Conservation of a room: A treatment proposal for Mark Rothko's Harvard Murals. (1st November 2016) - Stenger, Jens; Khandekar, Narayan; Raskar, Ramesh; Cuellar, Santiago; Mohan, Ankit; Gschwind, Rudolf
Abstract : A treatment with projected light for Mark Rothko's Harvard Murals (1962) is proposed. The group of five paintings on canvas has changed color due to the presence of a fugitive red pigment and excessive exposure to natural light in a room with large windows. For the conservation of Rothko's Harvard room, it is brought into context within his other commissions and environments. The original color of the works is determined by the digital restoration of contemporary photographs. With a camera projector system a compensation image is calculated that is projected onto the original canvas resulting in a restored color appearance. This approach of inpainting with light is compared with considerations of cleaning and inpainting in conventional conservation treatments. Overall lighting and architecture including the unusual wall color carefully chosen by Rothko play a key role in the treatment of the Mural cycle as an environment.